Role of Serum Uric Acid as a Protective Biomarker in Patients with Different Histopathological Grades of Oral Squamous Cell Carcinoma: a Case-Control Study. (14th September 2020) - Manifar, Soheila; Rahimzamani, Arezoo; Shirkhoda, Mohammad; Ghamsari, Mohammad Nikkhah; Bakhshi, Mahin
Abstract : The antioxidant properties of uric acid may have a protective effect against the formation of oxygen radicals and subsequently against carcinogenicity. The present study aimed at evaluating the serum level of uric acid in patients with oral squamous cell carcinoma (OSCC) with different histopathological grades. In this descriptive-analytical, case-control study, patients with OSCC and healthy controls were selected and matched regarding age and gender. The serum samples were collected from patients (before radiotherapy and chemotherapy) and controls, and their serum uric acid levels were measured enzymatically. Data were analyzed using independent t -test and ANOVA at 0.05 level of significance. The mean serum uric acid level in OSCC patients (4.2 ± 1.5 mg / dL ) and healthy controls (4.38 ± 1.22 mg / dL ) was not significantly different (P = 0.377 ). No significant association was noted between the histopathological grade of OSCC and mean serum uric acid (P = 0.781 ). The serum uric acid level had a direct significant correlation with age in OSCC patients (P < 0.001 ). The results of this study did not support the role of uric acid as a protective biomarker in OSCC. Further prospective studies are recommended to better elucidate the role of uric acid in the etiology of OSCC.